2015
DOI: 10.1002/pola.27682
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polycarbosilanes having sugar-derived structures as novel materials for cell cultivation

Abstract: Polycarbosilanes with or without sugar-derived structures in the polymer side chains were synthesized and their application to materials for cell cultivation was investigated. Polysilacyclobutanes having glucose-derived moieties or N-acetylglucosamine-derived moieties (polyBMSB-glucose and polyBMSB-AGA) were synthesized by ene-thiol reaction between precursor poly(1-(3-butenyl)21-methylsilacyclubane) (polyBMSB) and tetraacetylglucose or tetraacetylglucosamine having a thiol group at the anomeric position and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Silacyclobutane rings with Si−Cl side groups can be synthesized through Grignard chemistry and further functionalized to contain various chemical moieties. Some examples include 5membered cyclic carbonates for electrolyte applications, 157,158 carbohydrate derivatives for bioapplications, 159,160 epoxyfunctionalized polycarbosilanes for elastomer development, 161 and styrene or benzocyclobutene derivative low-dielectric insulating materials. 162 BCPs continue to be an area of interest, particularly synthesizing polystyrene/polycarbosilane blocks through anionic ROP, as they can undergo phase separation into microdomains.…”
Section: Chemical Reviews Pubsacsorg/crmentioning
confidence: 99%
“…Silacyclobutane rings with Si−Cl side groups can be synthesized through Grignard chemistry and further functionalized to contain various chemical moieties. Some examples include 5membered cyclic carbonates for electrolyte applications, 157,158 carbohydrate derivatives for bioapplications, 159,160 epoxyfunctionalized polycarbosilanes for elastomer development, 161 and styrene or benzocyclobutene derivative low-dielectric insulating materials. 162 BCPs continue to be an area of interest, particularly synthesizing polystyrene/polycarbosilane blocks through anionic ROP, as they can undergo phase separation into microdomains.…”
Section: Chemical Reviews Pubsacsorg/crmentioning
confidence: 99%
“…Polycarbosilanes have many unique properties such as high flexibility, excellent thermal stability, chemical and electrochemical stability, , so they can be potential key polymers for novel functional materials. We recently reported applications of polycarbosilanes to prepare gel polymer electrolytes for lithium ion batteries and to other soft network-forming materials. , We have also investigated polycarbosilanes having sugar-derived structures in the polymer side chains and evaluated whether they could be used as biocompatible materials …”
Section: Introductionmentioning
confidence: 99%
“…17,18 We have also investigated polycarbosilanes having sugarderived structures in the polymer side chains and evaluated whether they could be used as biocompatible materials. 19 Polycarbosilanes having 5-membered cyclic carbonate groups in their side chains are expected to be good candidates of new SPE matrices. We synthesized polycarbosilanes having one or two cyclic carbonate groups per repeating unit and examined their ionic conductivity as well as their thermal properties in the presence or absence of lithium salts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In attempt to create novel biomaterials, we introduced sugar moieties into soft, stable, and biologically inactive polycarbosilanes. We synthesized polycarbosilanes having glucose or acetylglucosamine moieties in the repeating units, and confirmed their low cytotoxicity by cell culture tests . We also demonstrated that networked polymers, which may be useful for material applications, can be effectively prepared by crosslinking the polymer with a diisocyanate …”
Section: Introductionmentioning
confidence: 72%
“…Poly(1‐(3‐butenyl)‐1‐methylsilacyclobutane) (PSB, M n = 8700 M w = 9700 relative to polystyrene standards), 2,3,4,6‐tetra‐ O ‐acetyl‐β‐ d ‐galactopyranosyl‐(1–4)‐2,3,6‐tri‐ O ‐acetyl‐thio‐β‐ d ‐glucopyranoside (HALac‐SH), polycarbosilane having a glucose derived structure (PSB‐Glc), and poly(1‐(3‐hydroxybutyl)‐1‐methylsilacyclobuane) (polyHBMSB) were prepared according to the reported procedure . AIBN, 28% sodium methoxide methanol solution, hexamethylene diisocyanate (HMDI), toluene, ethyl acetate, diethyl ether, DMSO, DMF, N , N ‐dimethylacetamide (DMAc), acetone, methanol, and hexane were purchased from Wako Pure Chemical Industry (Osaka, Japan) and used as delivered.…”
Section: Methodsmentioning
confidence: 96%